Design and development of galantamine hydrobromide transdermal patch for treatment of alzheimer’s disease - Woo, Fong Yen (2015)
Alzheimer’s disease (AD) is a neurodegenerative disease, which is caused by abnormal accumulation of beta amyloid (Aβ) peptide in brain and degeneration of cholinergic neurons. Galantamine hydrobromide (GH) is an effective drug for the treatment of AD with its function as the acetylcholinesterase enzyme (AChE) inhibitor. It is currently prescribed through oral and parenteral delivery in the form of tablets, capsules and solutions. These administration methods of GH can cause unwanted effects such as disturbed sleep, vomiting and nausea. These effects can be reduced by using transdermal delivery of GH, which are more patient compliance, more controlled drug release, less frequent drug dosing and longer treatment time. GH was first formulated in gel drug reservoir and then fabricated in the three-layered patch system. HPLC analysis confirmed the loading of GH in the prepared gel. Preliminary studies showed that amount of carbopol, triethanolamine (TEA), GH and propylene glycol (PG) can affect the drug release from gel. Higher drug release was observed when gel consisted of lower amount of carbopol and TEA, with higher amount of GH and PG. Response surface methodology (RSM) based on central composite design (CCD) proposed that optimized gel consisted of 0.89% w/w carbopol, 1.16% w/w TEA and 4.19% w/w GH gave predicted cumulative drug release amount at 8 h (Q8) of 17.80 mg.cm-2 and permeation flux (J) of 2.27 mg.cm-2/h. These values were closely fitted to the actual values of Q8 (16.93 ± 0.08 mg.cm-2) and J (2.32 ± 0.02 mg.cm-2/h). The results from artificial neural network (ANN) gave insignificant standard deviations between actual with predicted Q8 (16.23 mg.cm-2) and J (2.17 mg.cm-2/h). The importance chart obtained from ANN revealed that the carbopol and TEA amount were the main factors affecting Q8 and J. FTIR study showed the interactions between GH with other compositions in gel. The physicochemical evaluations showed the moderate pH, successful drug loading and high moisture content in gel. Rheological studies proved the elastic network structure of GH-loaded gel, with the presence of nonNewtonian behaviour, shear thinning properties and temperature-dependent viscosities. The porous network structure of gel formulation was confirmed with TEM analysis. Toxicity test on fibroblast cells found that the gel was skin compatible. The GH-loaded gel was then fabricated into the patch system. This system consisted of backing layer, gel drug reservoir in pad layer and release liner. The size of patch is 6 cm  7 cm, while the size of gel drug reservoir layer is 2 cm  3 cm. Thickness of this patch is 0.2 cm and loaded with 13.97 mg/cm2 of GH. This patch had neutral pH, successful drug loading and high moisture content. Histological examinations showed there was no irritation on rat skins after application of the patch. GH release from gel and patch system provided more controlled and sustained drug release compared to the control, with the involvement of super case-II transportation. Both GH-loaded systems exhibited good inhibition of AChE activities. Stability evaluation on GH-loaded gel and patch systems revealed the high stability of both systems under centrifugation. Both systems were unstable at 4 °C and 45 °C, but stable at 25 °C. The systems were physically stable, with no crystals formation and no phase separation for at least 6 months at 25 °C. The systems also showed insignificant changes in pH, drug content and moisture content through 6 months of storage. pH studies showed gel and patch formulations had pH ranged from 6.84 to 7.12, which would not cause skin irritation. Drug loading and moisture content analysis proved the successful drug loading and high moisture content in gel and patch system, with less than 10% drug and moisture loss. Therefore, it can be concluded that both GH-loaded systems were stable and potent to be used for the treatment of AD.